Intra‐arterial chemoradiotherapy for locally advanced buccal mucosal cancer in an elderly patient with multiple comorbidities: A case report. Issue 9 (25th May 2022) - Taniguchi, Akito; Toyomasu, Yutaka; Takada, Akinori; Mase, Takamitsu; Kurohara, Kazuto; Omori, Kazuki; Nanpei, Yui; Kawamura, Tomoko; Sakuma, Hajime; Nomoto, Yoshihito
Abstract: Background: The management of locally advanced oral cavity squamous cell carcinoma (LA‐OCScc) in elderly patients with multiple comorbidities is difficult. Case: We report the case of an elderly patient with buccal mucosal squamous cell carcinoma as well as chronic renal dysfunction, hepatic cirrhosis, rheumatoid arthritis, and metachronous diffuse large B‐cell lymphoma. We performed radiation therapy (a total dose of 70 Gy in 35 fractions) and six cycles of intra‐arterial chemotherapy with 40 mg/m 2 cisplatin per week. After treatment, the tumor completely disappeared, and there was no recurrence or deterioration of comorbidities during the 12‐month follow‐up period. Conclusion: Intra‐arterial chemoradiotherapy may be a good treatment option for LA‐OCScc in elderly patients with multiple comorbidities.